Vitamin D3/VDR alleviates double-stranded RNA virus -induced biliary epithelial cell damage by inhibiting autophagy - Na Liu; Pu Zhao; Ping Cao; JunPeng Hui; YongKang Pan; Jiwen Cheng (BMC Gastroenterology)
Abstract Background The increased apoptosis of bile duct epithelial cells (BECs) due to some damage factors is considered the initiating factor in the occurrence and progression of biliary atresia (BA). Vitamin D receptor (VDR) is thought to play a crucial role in maintaining the intrinsic immune balance and integrity of bile duct epithelial cells (BECs). To investigate the role of VDRs in the pathogenesis and progression of BA using in vitro and in vivo models. Materials and methods The VDR expression levels in intrahepatic bile duct epithelial cells (IBDECs) in pediatric patients with BA were examined using immunohistochemical analysis. The correlation of the VDR levels with the incidence of refractory cholangitis after Kasai portoenterostomy (KPE) and the autologous liver survival time was analyzed. The levels of genes and proteins involved in related pathways were examined using quantitative real-time polymerase chain reaction and western blotting, respectively. The secretory levels of inflammatory factors were analyzed using enzyme-linked immunosorbent assay. A BA mouse model was established through the intraperitoneal sequential injection of rhesus rotavirus (RRV). The role of VDR in the pathogenesis and progression of BA was examined using in vitro and in vivo models. Retrospective analysis of patients with BA to examine the therapeutic efficacy of VDR activators on BA. Results 15 pediatric BA patients exhibiting VDR downregulation in IBDECs showed a higher incidence of refractory cholangitis after Kasai portoenterostomy (p = 0.037) and a lower native liver survival time compare to 23 BA patients without VDR downregulation (p = 0.032). 1,25-VD3 inhibited the degree of autophagy induction in HIBECs by poly(I: C) (p < 0.05), mitigated poly(I: C)-induced BEC damage and apoptosis by inhibiting autophagy (p < 0.05). 1,25-VD3 significantly suppressed the poly(I: C)-induced downregulation of SRC (p < 0.05) and ERK1/2 phosphorylation (p < 0.05). 1,25-VD3 exert a protective effect against RRV-induced BEC damage by inhibiting autophagy in BA mouse model. The incidence of cholangitis and the native liver survival time after surgery in the calcitriol-treated group was significantly lower than that in the control group. (p = 0.033, p = 0.035, respectively). Conclusions VDR activator mitigated dsRNA-induced BEC damage and apoptosis by inhibiting autophagy in vitro and in vivo. The 1,25-VD3/VDR/Src axis alleviated poly(I: C)-induced HIBEC damage and apoptosis through the PLA2/PKC/ERK pathway. Graphical abstract